Fluvial avulsions influence soil fertility in the Pantanal wetlands (Brazil) - Louzada, Rômullo Oliveira; Bergier, Ivan; McGlue, Michael M.; de Oliveira Roque, Fabio; Rasbold, Giliane; Domingos-Luz, Leandro; Lo, Edward; Assine, Mario Luis [UNESP] (Elsevier, 2024)
River avulsions drive important changes in the Pantanal wetlands, owing to their role in the hydro-sedimentology of the region. Although relevant to numerous ecosystem services, few studies have analyzed the influence of river avulsions on soil fertility in the Pantanal. Here, we use the largest ongoing avulsion in the Taquari River (Caronal region) to evaluate the effects on soil fertility, considering two factors: avulsion stage (1) and aquatic-terrestrial succession (2). Since both factors are influenced by macrophyte abundance, an incident map was created through tasseled cap indices from Sentinel 2 images to guide sampling efforts in flooded soils. The mapped area was split into two zones of alluvial processes, the first from the apex of the Caronal lobe corresponding to the Taquari River megafan (TRM), and the second as the distal Paraguay River floodplain (PRF). Soil macro- and micronutrient levels were evaluated from 42 surface samples (0–0.2 m) distributed across the two alluvial process zones. The macrophyte map's overall accuracy (OA) was analyzed by a confusion matrix using the Sentinel 2 imagery. Finally, we used Random Forest regressions to determine the influence of response variables on soil attributes, including tassel indices, distance from the Caronal crevasse, macrophyte density, and an existing soil fertility map. The macrophyte map obtained an OA of 93 %. Some parameters such as pH (r = −0.62; R2 = 0.57), effective cation exchange capacity (r = −0.49; R2 = 0.79), Mn (r = −0.71; R2 = 0.6), Zn (r = −0.69; R2 = 0.54), and base saturation (r = −0.7; R2 = 0.93) were influenced by the distance or level of maturation of the avulsion stage in the TRM. Our scattering of soil collections was insufficient to test the terrestrialization hypothesis (2). The study results show that river channel avulsions influence the accumulation of mineral and organic nutrients in tropical floodplain soils, which has implications for fertility and biodiversity.
Keywords: Ecosystem services; Flooding; Macrophytes; Organic matter; Sediment retention